Benthic Foraminifera Composition in Coral Reef Areas at Malalayang Beach Waters - Alam, Muhammad Reza Sinar; Mamuaja, Jane M.; Windarto, Agung B.; Mantiri, Rose O. S. E.; Schaduw, Joshian N. W. (Sam Ratulangi University, 2024)
Malalayang Beach is part of the coastal area of Manado Bay and is situated in the North Sulawesi Province of Indonesia. The coral reef ecosystem is one of the coastal ecosystems with high biodiversity. The uniqueness of the ecosystem and the diversity of its organisms make coral reef ecosystems have high social, ecological, and economic values. In 1998, the Environmental Protection Agency (EPA) of the United States recommended the use of foraminifera as indicators for aquatic assessments. Foraminifera is a meiobenthic components at the bottom of the sea that act as producer of calcium carbonate (CaCO3) in sediments in the benthic and pelagic zones of the sea. The purpose of this study was to study at the composition of benthic foraminifera based on their genus in the waters of Malalayang Beach and also assess the condition of coral reef waters on Malalayang Beach using the FoRAM Index. This research was carried out by taking sediment samples in Malalayang Beach in nine sampling points at a depth of 5–8.5 m. The samples were then washed and sorted to obtain foraminifera tests. From 2,830 successfully identified specimens, 17 genera were obtained with FoRAM index values ranging from 5.46 to 9.53. The average value of the FoRAM Index at Malalayang Beach is 7.32, indicating that the waters of Malalayang Beach are still suitable for coral growth. Keywords: Malalayang Beach, Foraminifera, Coral Reef, FoRAM Index Abstrak Pantai Malalayang adalah bagian dari Teluk Manado yang terletak di Sulawesi Utara, Indonesia. Ekosistem terumbu karang merupakan salah satu ekosistem pesisir dengan biodiversitas yang tinggi. Keunikan ekosistem serta keragaman organismenya menjadikan ekosistem terumbu karang memiliki nilai sosial, ekologi dan ekonomi yang tinggi. Environmental Protection Agency (EPA) dari Amerika Serikat menyarankan penggunaan foraminifera sebagai indikator penilaian perairan pada tahun 1998. Foraminifera merupakan komponen meiobentik di dasar perairan yang berperan sebagai penghasil kalsium karbonat (CaCO3) pada sedimen yang ada di zona bentik dan pelagis laut. Tujuan penelitian ini adalah untuk mempelajari komposisi foraminifera bentik berdasarkan genusnya pada perairan Pantai Malalayang dan juga menilai kondisi perairan terumbu karang di Pantai Malalayang menggunakan Indeks FoRAM. Penelitian ini dilakukan dengan cara mengambil sampel sedimen di perairan Pantai Malalayang pada sembilan titik pengambilan sampel dengan kedalaman 5 - 8,5 m. Selanjutnya sampel dicuci dan disortir untuk mendapatkan cangkang foraminifera. Dari sejumlah 2830 spesimen yang berhasil diidentikasi, diperoleh sebanyak 17 genus dengan nilai indeks FoRAM berkisar dari 5,46 - 9,53. Nilai rata-rata indeks FoRAM pada Pantai Malalayang adalah 7,32 dan ini mengindikasikan bahwa perairan Pantai Malalayang masih baik dan layak untuk pertumbuhan karang. Kata Kunci : Pantai Malalayang, Foraminifera, Terumbu Karang, Indeks FoRAM